2011
DOI: 10.1007/s00726-011-1004-1
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine analogs modulate gene expression by inhibiting lysine-specific demethylase 1 (LSD1) and altering chromatin structure in human breast cancer cells

Abstract: Aberrant epigenetic repression of gene expression has been implicated in most cancers, including breast cancer. The nuclear amine oxidase, lysine-specific demethylase 1 (LSD1) has the ability to broadly repress gene expression by removing the activating mono- and di-methylation marks at the lysine 4 residue of histone 3 (H3K4me1 & me2). Additionally, LSD1 is highly expressed in estrogen receptor α negative (ER−) breast cancer cells. Since epigenetic marks are reversible, they make attractive therapeutic target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 31 publications
3
53
0
Order By: Relevance
“…Incubating Drosophila S2 cells for 3 days in media containing 40 μM and 80 μM bisguanidine polyamine analog, which inhibits human LSD1 in breast cancer cells (Zhu et al, 2012), significantly increased their H3K4me1 level, as expected, and also increased their H3K27ac level, while CBP and H3K4me3 levels were unchanged (Fig. 7D, lanes 4 and 5).…”
Section: Research Articlesupporting
confidence: 69%
“…Incubating Drosophila S2 cells for 3 days in media containing 40 μM and 80 μM bisguanidine polyamine analog, which inhibits human LSD1 in breast cancer cells (Zhu et al, 2012), significantly increased their H3K4me1 level, as expected, and also increased their H3K27ac level, while CBP and H3K4me3 levels were unchanged (Fig. 7D, lanes 4 and 5).…”
Section: Research Articlesupporting
confidence: 69%
“…A role for elevated expression of LSD1 has been implicated in tumorigenesis in various cancers including breast cancer (3, 59). Studies from our and other laboratories consistently showed that inhibition of LSD1 hindered proliferation of breast cancer cells (6, 8, 10). Lim et al reported that LSD1 is highly expressed in ER-negative breast cancers (6).…”
Section: Introductionsupporting
confidence: 56%
“…They promote re-expression of silenced genes of the GATA family of transcription factors that are important in the development of colon cancers [48]. These LSD1 inhibitors alter promoter activity of multiple genes in breast cancer cells and are postulated to have considerable therapeutic potential [49]. …”
Section: Histone Modifications and Breast Cancermentioning
confidence: 99%